Social and economic convergence in the EU, 1990-2017 - Dan Constantin Olteanu (Romanian Academy, National Institute for Economic Research, 2019)
The present study represents an empirical analysis of the well-being convergence between EU Member States, using a set of 14 socio-economic indicators, grouped into 4 categories: population health status; financial situation of households; social conditions; education. To these we added the gross domestic product per capita, for comparison between economic and welfare convergence. We also aim to highlight the dynamics of the gap between the Eastern and Western European countries, as well as the evolution of convergence within these two groups. For the last 10 years analyzed, more precisely in the period 2007-2017, the calculation of standard deviation indicates a tendency of convergence within the EU, for 11 of the 14 welfare indicators analyzed. The variation within the group of Eastern European countries is higher than that recorded between the Western European countries, in 9 of 14 indicators. There is also a tendency for convergence between the two groups although, for some indicators (including GDP), the trends corresponding to their averages tend to remain parallel.
Keywords: I31; I15; I25; O47; 330; social convergence; economic convergence; welfare